Cannabis Glandular Trichome Cell Walls Undergo Remodeling to Store Specialized Metabolites - Livingston, Samuel J; Bae, Eun Jeong; Unda, Faride; Hahn, Michael G; Mansfield, Shawn D; Page, Jonathan E; Samuels, A Lacey (Plant and cell physiology, 2021)
Abstract The valuable cannabinoid and terpenoid metabolites of Cannabis sativa L. are produced by floral glandular trichomes. The trichomes consist of secretory disk cells, which produce the abundant lipidic metabolites, and an extracellular storage cavity. The mechanisms of apoplastic cavity formation to accumulate and store metabolites in cannabis glandular trichomes remain wholly unexplored. Here, we identify key wall components and how they change during cannabis trichome development. While glycome and monosaccharide analyses revealed that glandular trichomes have loosely bound xyloglucans and pectic polysaccharides, quantitative immunolabeling with wall-directed antibodies revealed precise spatiotemporal distributions of cell wall epitopes. An epidermal-like identity of early trichome walls matured into specialized wall domains over development. Cavity biogenesis was marked by separation of the subcuticular wall from the underlying surface wall in a homogalacturonan and α-1,5 arabinan epitope-rich zone and was associated with a reduction in fucosylated xyloglucan epitopes. As the cavity filled, a matrix with arabinogalactan and α-1,5 arabinan epitopes enclosed the metabolite droplets. At maturity, the disk cells’ apical wall facing the storage cavity accumulated rhamnogalacturonan-I epitopes near the plasma membrane. Together, these data indicate that cannabis glandular trichomes undergo spatiotemporal remodeling at specific wall subdomains to facilitate storage cavity formation and metabolite storage.